Decentralized Urban Governance and Environmental Collaboration in South Korea: The Case of Hyundai City, Ulsan - BAE, Yooil (Institutional Knowledge at Singapore Management University, 2013)
This paper explores how decentralization has created a “local political arena” and has been transforming governance in the environmental management sector in South Korea. Korea has been known as a developmental state where the strong central government and businesses have conspicuously dominated during most of its industrialization period. Yet, the deepened democracy, global competitiveness and fiscal austerity have pressured central political stakeholders to devolve highly centralized functions and authority to local bodies since the mid-1990s. The building of democratic institutions at the local level, including directly elected mayors and city councils, has created room for local politics and diminished central political leverage over local affairs. The national economic crisis has highlighted the inefficiency of the centralized system and encouraged further administrative and fiscal decentralization under the democratic governments. In this context while the central government and big businesses continue to have a significant say in policy making, local executives, with their expanded decisional authority and resources, are trying to improve the images of their cities and to take responsibility for promoting urban economies and improving quality of life in the age of trans-border links and competition. This paper analyzes the case of Ulsan, where Hyundai and several other conglomerates are located and which has been a symbol of state-led industrialization during most of the development period. Despite the large role played by the centre in the development of Ulsan, the empowered mayor of the city has successfully turned citizens’ attention to post-industrial aspects of governance for ensuring the future competitiveness of the city in global markets by orchestrating collaborative implementation of environmental policies. The paper explores how this governance shift in Ulsan has led successful collaborative environmental change by mobilizing local businesses, civic organizations and general citizens who might not have been interested in the making of an “environment-friendly city.